ICTs use and library information resources in enhancing a sustainable educational development: a case study of University of Ibadan, Ibadan, Nigeria (2018)
Education is an asset that an individual must possess and acquire because it is an instrument par excellence for national development. The use of Information and Communication Technology has advanced the education sector in Nigeria mostly in tertiary institutions as a result of information provision. This study therefore investigates ICTs use and library information resources in enhancing a sustainable educational development in the University of Ibadan, Nigeria. Survey research method was adopted for the study; undergraduate students of University of Ibadan were selected for this study. Data collected were analyzed using frequency count, analysis of variance (ANOVA), regression and correlation statistical tool to test for the relative contribution and the significant relationship between ICTs use, library information resources to the prediction of sustainable educational development tested at 5% level of significance. The results revealed that Information and Communication Technology (ICT) has contributed to the development of education in the study area with Computer (Laptop) 341(97.7%) which ranked highest. The findings also revealed that the use of library information resources by the undergraduates was very highly utilized with textbook 219 (62.8%) which ranked highest. The findings reveal that reading for examination 349(100.0%) was the major purpose of using information resources by the undergraduate. It also revealed limited number of computers 314(90.0%) as one of the major constraints of information resources utilisation in the university. The study revealed that there was a significant combined effect of the independent variables on the dependent variable, (F (2,346) = 7.724, P<0.05). It also revealed that information resources use (Beta = .203, t=3.860, p<0.05) and ICT use (Beta =.149, t=1.515, p>0.05) are potent predictor factors of educational development. It further revealed that information resources use (r =.201**, p<0.05) and ICT use (r =-. 147**, p<0.05) positively correlated to the prediction of educational development of students. The study recommended that government should make computer and internet facilities available at all levels of our educational system as this is expected to improve the academic performance of students in our higher institutions.